Enhancing the learning of evolutionary anthropology skills by combining student‐active teaching with actual and virtual immersion of Master's students in fieldwork, laboratory practice, and dissemination. Issue 4 (15th April 2022) - Bayle, Priscilla; Armand, Dominique; Bessou, Maryelle; Cochard, David; Couture, Christine; Deguilloux, Marie‐France; Ferrier, Catherine; Haget, Cathy; Jaubert, Jacques; Knüsel, Christopher; Martins, Stéphanie; Pubert, Éric; et al.
Abstract: Higher education in evolutionary anthropology involves providing students with in‐depth knowledge of biological and cultural heritage sites and collections that are frequently inaccessible. Indeed, most sites, fossils, and archaeological remains can be visited or manipulated only rarely and solely by specialists with extensive experience. Owing to the development of 3D and medical imaging techniques, this fragile heritage is now more widely accessible, and in a dynamic way. However, exclusive adoption of virtual teaching and learning has a negative impact on student engagement and, naturally, on exchanges with instructors, and thus cannot be used without some reservations. In the ITAP ( Immersion dans les Terrains de l'Anthropologie biologique et de la Préhistoire ) project of the higher education STEP ( Soutien à la Transformation et à l'Expérimentation Pédagogiques ) transformation program at the University of Bordeaux, we combine student‐active teaching with Master's students fully immersed in ongoing fieldwork, laboratory study, and dissemination of research results in order to develop more individually shaped learning curricula and to foster both professional and new interdisciplinary skills. Here, we present examples of experiments conducted in the ITAP project using both authentic and virtual collections of archaeological, experimental, and reference materials that help to break down the barriers between research activities and higher education, as well as providing a more general appraisal of the appropriate use of virtual tools in higher education by combining them with real‐life situations. Abstract : The article describes examples of novel teaching methods that we have developed in our Master's program in evolutionary anthropology, where we combine student‐active teaching with Master's students fully immersed in ongoing fieldwork, laboratory study, and dissemination of research results.